2019
DOI: 10.1002/app.47610
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, wear, and dielectric behavior of TiO2 reinforced high‐density polyethylene composites

Abstract: Almost fully dense high-density polyethylene (HDPE) reinforced with submicron-sized titanium dioxide (TiO 2 ) ceramic filler (up to 40 vol %) was fabricated using compression molding. More than 98.5% ρ th (theoretical density) could be obtained for all the HDPE compositions and its measured density varied between 0.94 and 2.25 g cc −1 . The hardness of HDPE increased considerably from 32.6 to 69 MPa (i.e., by two times) with the addition of 40 vol % TiO 2 . The compression strength (19.03-34.16 MPa) and modulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The relations among the hydroxyl groups of ZnO and TiO 2 and the CH group of HDPE allow hydrogen sticking among reinforcement and matrix in HDPE/ZnO/TiO 2 composites. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…The relations among the hydroxyl groups of ZnO and TiO 2 and the CH group of HDPE allow hydrogen sticking among reinforcement and matrix in HDPE/ZnO/TiO 2 composites. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…It could be observed from B3 that friction surfaces were filled with TiO 2 , which not only make up the surface abrasion, but also optimize the surface geometry roughness, so the overall friction coefficient and abrasion loss were relatively low. The widely accepted anti-wear theories were ball effect, filling and repairing effect and third body protection [29,30,31]. Nano-TiO 2 had the effect of reducing the friction coefficient, decreasing abrasion and repairing wear defects [32].…”
Section: Resultsmentioning
confidence: 99%
“…Nabhan et al [10] investigated the roll of nano Al2O3 particles with different weight fractions varies between 0.1and 0.5 on the tribological properties of HDPE composites, a noticeable improvement in hardness, coefficient of friction, and wear resistance accompanied the increasing in nano Al2O3 content. Shaji et al [11] evaluated the effect of adding titanium dioxide on the mechanical and tribological properties of HDPE composites, they indicated that the increasing the titanium weight fraction improved the mechanical properties as well as the wear resistance in comparative to pure HDPE. Mahboba and Al-Shammari [12] indicated a clear improvement in wear resistance due to the addition of hybrid nanofillers consisting of Alumina and Zirconia p articles to HDPE composites, which is suggested to design a hip joint replacement with more than 15 years of estimation life.…”
Section: Introductionmentioning
confidence: 99%
“…Joseph and Panneerselvam [15] considered Taguchi method to select the optimum operating conditions of HDPE reinforced with tungsten particles under the influence of abrasive wear; the increase in tungsten percentage limited the effect applied load and sliding distance and caused a clear decrease in wear rate. Hence, the percent work aimed to use Taguchi method to optimize the best working conditions of HDPE reinforced with nano alumina particles under the influence of wear behavior used in hip joint replacements that are not covered by references [8][9][10][11] as well as a surface topography analysis will be considered to understand the mechanism of wear failure in HDPE and their composites.…”
Section: Introductionmentioning
confidence: 99%